ICSECS and ICoCSIM discuss efforts to empower digital community with advanced technology - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 22 September 2021 - The Fourth Industrial Revolution (IR4.0) and the rapid development of disruptive technologies including digital technology are seen to have the potential to change the economic and social landscape around the world.